Reciprocal Relationship Between Parenting Styles and Interpersonal Personality in Chinese Adolescents - Fan, Weiqiao; Li, Mengting; Chen, Xinyin (Frontiers in Psychology, 2021)
This study examined the reciprocal relations between the parenting styles and adolescents' interpersonal personality in China. A total of 722 sixth-grade Chinese junior high school students reported their interpersonal relatedness (IR) personality trait and perceived parenting styles of their parents. Of these students, 411 completed the survey again in eighth grade. One parent of each student rated their parenting styles. The results indicated that perceived paternal rejection negatively predicted adolescents' IR 2 years later, whereas perceived paternal behavioral controlling positively predicted adolescents' IR 2 years later. IR also positively predicted perceived paternal warmth 2 years later. Significant reciprocal association between adolescents' IR and perceived maternal rejection was found. Parent-rated behavioral control negatively predicted adolescents' IR, whereas Parent-rated filial piety positively predicted adolescents' IR. The results were discussed in the Chinese context.